Perbandingan Kualitas Citra Hard Copy Dengan Hasil Digitizer Dan Kamera Saku Pada Foto Polos Osteoarthritis Genu Di Bagian Radiologi Rsup Dr.Sardjito - SYAWALUDDIN, Abdul Jabar Yusuf ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background : One of the supporting diagnosis of osteoarthritis is the x-rays. But with Indonesia's geographical situation and the number of radiology specialists inadequate, it appears the idea of the use of teleradiology. Teleradiology must be supported by good imaging results so that the resulting image does not lead to biased interpretation. Objective : To determine differences in image quality and appropriateness of diagnosis between films with hard copy and soft copy of the digitizer soft copy of the pocket camera on the photo Genu Osteoarthritis. Methods and Materials : an observational study on 25 osteoarthritis genu plain. Digital data in the print work station using a laser printer to produce a hard copy which is then digitized using a digitizer and a pocket camera. The image quality compared to the hard copy soft copy image quality results using the digitizer digitizing and pocket cameras. Results : The group has a hard copy image quality mean 7.76, standard deviation 1:26, 6:00 minimum value, maximum value of 9:00 with the Shapiro - Wilk test of 0.000. Image quality digitizer group had a mean 7.72, standard deviation 1:27, 5:00 minimum value, maximum value of 9:00 with the Shapiro - Wilk test of 0.002. Group picture quality pocket camera has a mean of 6.68, standard deviation 1.67, minimum value of 4:00, 9:00 with the maximum value of the Shapiro - Wilk test of 0.026. Appropriateness of the diagnosis group had a mean hard copy 4.76, standard deviation 1:26, 3:00 minimum value, maximum value of 6:00 with the Shapiro - Wilk test of 0.000. Appropriateness of the diagnosis group had a mean 4.72 digitizer, standard deviation 1:27, 2:00 minimum value, maximum value of 6:00 with the Shapiro - Wilk test of 0.002. Kelompom suitability pocket camera diagnosis had a mean 4.72, standard deviation 1:27, 3:00 minimum value, maximum value of 6:00 with the Shapiro - Wilk test of 0.000. Conclusions : There was no difference in image quality between the statistically significant with a hard copy to soft copy digitizer digitizing results on plain radiography of osteoarthritis genu. There is a difference in image quality between the statistically significant with a hard copy to soft copy of digitizing results on plain pocket camera osteoarthritis genu ie hard copy has better image quality. There were no differences suitability diagnosis was statistically significant between the hard copy to soft copy of the digitizer or digitizing with a pocket camera in plain radiography of osteoarthritis genu.